Antiplatelet therapy prior to COVID-19 infection impacts on patients mortality: a propensity score-matched cohort study - Mateusz Sokolski; Konrad Reszka; Barbara Adamik; Katarzyna Kilis-Pstrusinska; Weronika Lis; Michał Pomorski; Janusz Sokolowski; Adrian Doroszko; Katarzyna Madziarska; Ewa Anita Jankowska; Marcin Protasiewicz (Scientific Reports, 2024)
Abstract One of the major pathomechanisms of COVID-19 is the interplay of hyperinflammation and disruptions in coagulation processes, involving thrombocytes. Antiplatelet therapy (AP) by anti-inflammatory effect and inhibition of platelet aggregation may affect these pathways. The aim of this study was to investigate if AP has an impact on the in-hospital course and medium-term outcomes in hospitalized COVID-19 patients. The study population (2170 COVID-19 patients: mean ± SD age 60 ± 19 years old, 50% male) was divided into a group of 274 patients receiving any AP prior to COVID-19 infection (AP group), and after propensity score matching, a group of 274 patients without previous AP (non-AP group). Patients from the AP group were less frequently hospitalized in the intensive care unit: 9% vs. 15%, 0.55 (0.33–0.94), developed less often shock: 9% vs. 15%, 0.56 (0.33–0.96), and required less aggressive forms of therapy. The AP group had more coronary revascularizations: 5% vs. 1%, 3.48 (2.19–5.55) and strokes/TIA: 5% vs. 1%, 3.63 (1.18–11.2). The bleeding rate was comparable: 7% vs. 7%, 1.06 (0.54–2.06). The patients from the AP group had lower 3-month mortality: 31% vs. 39%, 0.69 (0.51–0.93) and didn’t differ significantly in 6-month mortality: 34% vs. 41%, 0.79 (0.60–1.04). When analyzing the subgroup with a history of myocardial infarction and/or coronary revascularization and/or previous stroke/transient ischemic attack and/or peripheral artery disease, AP had a beneficial effect on both 3-month: 37% vs. 56%, 0.58 (0.40–0.86) and 6-month mortality: 42% vs. 57%, 0.63 (0.44–0.92). Moreover, the favourable effect was highly noticeable in this subgroup where acetylsalicylic acid was continued during hospitalization with reduction of in-hospital: 19% vs. 43%, 0.31 (0.15–0.67), 3-month: 30% vs. 54%, 044 (0.26–0.75) and 6-month mortality: 33% vs. 54%, 0.49 (0.29–0.82) when confronted with the subgroup who had acetylsalicylic acid suspension during hospitalization. The AP may have a beneficial impact on hospital course and mortality in COVID-19 and shouldn’t be discontinued, especially in high-risk patients.